Smart automation feeding control for fish farm - Nik Nur Ezzahazyyatie, Nik Mat (2022)
This thesis is about an automated system that was created using the Internet of Things (IoT). The main purpose of this project is to automate the feeding of fish using an Arduino microcontroller, as well as to collect data on water turbidity in fishponds. The Blynk app allows you to virtually observe all data related to water turbidity. Due to a shortage of personnel or the maintenance of too many fishponds, many fish farmers neglect to feed the fish. Furthermore, the cost of paying labor and wages is quite expensive. To avoid water turbidity exceeding water life limits, water quality must also be assessed in its natural state. Water is also important for the fish's health since it provides them with essential nutrients for their well-being.